2016
DOI: 10.1186/s13006-016-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding among city-dwelling professional working mothers in Ghana

Abstract: BackgroundIn Ghana, periodic national surveys report the practice of exclusive breastfeeding (EBF) in the general population to be over 50 %. However, little is known about EBF among professional working mothers, particularly its duration after maternity leave. Female workers are entitled to 12 weeks (84 days) of maternity leave with full pay in Ghana, and this can be extended by two additional weeks in case of a caesarean or abnormal delivery. This study assessed the prevalence of EBF, as well as factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
78
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 38 publications
17
78
5
4
Order By: Relevance
“…Evidence shows that employed mothers are less likely to EBF their infants for six months [ 37 , 38 ]. Dun-Dery et al also reported a very low proportion (10.3%) of EBF among city-dwelling professional working mothers in Ghana [ 19 ]. The low proportion of EBF found in our study could also be attributed to the cultural beliefs and misconceptions held about EBF as reported previously in rural Gambian settings [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that employed mothers are less likely to EBF their infants for six months [ 37 , 38 ]. Dun-Dery et al also reported a very low proportion (10.3%) of EBF among city-dwelling professional working mothers in Ghana [ 19 ]. The low proportion of EBF found in our study could also be attributed to the cultural beliefs and misconceptions held about EBF as reported previously in rural Gambian settings [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from another study conducted in Ghana also showed that although awareness on exclusive breast feeding among professional working mothers is almost universal (99 %), the practice of EBF at six months is low (10.3 %). 20 Elsewhere, Al-binali 21 found 89 % of mothers had a good knowledge about exclusive breastfeeding but only a small percentage (8.3%) engaged in the practice for the first six months. The same results can be drawn from our study which also shows higher level of knowledge of EBF (333 out of 400 women) but low practice of EBF (166 out of 400 women).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers were well-informed about exclusive breastfeeding and its benefits; however, the knowledge did not translate into practice. Based on the findings, these mothers may require more supportive post-delivery follow-ups [11].…”
Section: Review Of Related Literaturementioning
confidence: 94%